ACADEMIC APLICATION USING SMS GATEWAY - Irawan, Devi; Mayasari, Melati Suci (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
SMK Mutiara Mandiri Sungailiat is one of the health academic institutions that in data processing still using manually recordon a sheet of paper. It caused infrequent errors when inputting and processing of data that resulted infrequent loss of data or damage due data accumulation. At the time of academic in formation provision on students is still a way attached to the bulletin board that become in efficient because it canâ€™t be accessed anytime, anywhere. This research purpose is to make the academic Information Systems in SMK Mutiara Mandiri based sms gateway in order to facilitate the data processing. Research method used is data collecting that includes data observation and literature study, analysis of system requirements, system design, coding, and evaluation. The result from this research is to get an application takes in action after receiving SMS messages via mobile phones as the medium. Once processed by the computer, the results will be sent back to the sender of the request, also via mobile phones. In addition there is a broadcast system that serves to convey massal announcements or information. Broadcast is a facility that can only be used by the school.Â KeyWord : Sms Gateway, Mobile Applications, Java NetBeans, Mobile, Message